Deslocar para permanecer: implicações políticas das redes digitais nos processos criativos colaborativos - Albuquerque, Iara Cerqueira Linhares de (2016)
Digital networks like blogspot, wordpress and facebook have come to govern, with political and biopolitical implications, the new forms of living.Life has become a media environment, which makes the body a structuring axis of its existence.The problem that instigates this research is the paradox produced by the promise of democratization that the networks brought, reconfiguring the very concept of democracy, participation and sharing, but which did not prevent the mythification of the horizontality of communication as synonymous with the illuminist ideal of freedom, equality and fraternity (KATZ, 2014).The object taken here to investigate the transmediation in which such problem is expressed is done in the political reflections of the operation of the network environmentarticulating Clay Shirky (2011), and Castells (1999, 2003, 2013),in the proposal of subjectivity of Nikolas Rose (2011) and the imbrication between politics and life of Muniz Sodré (2002, 2006).The hypothesis is that although they are part of what Shirky calls the "culture of participation" (2011), there are fissures that indicate that the ways in which collaboration works in the digitally indexed world faces the difficulties / impossibilities that Esposito (2009, 2012)points to the "do together".Communicational activities in the network have produced immunization (Esposito, 2002) and ghettoization, reconfiguring the affectivity in various forms of social manifestations.With a qualitative methodology, which includes literature review and participation in one of the networks ctrl + alt + dança, the research will be supported in addition to the authors cited especially in the Corpomídia Theory (KATZ & GREINER) to investigate the role of the body in a possible transformation of consumers into collaborators andas an ecology of alternative possibilities of existence.Roberto Espósito (2009,2010), Maurizio Lazzaratto (2006,2013) and Paolo Virno (2010,2013) will demonstrate how the participation / collaboration networks in the digital environment are configured, and Helena Katz with the definition of indexed individual in which we are now part, will help us to analyze and test this new spatio-temporalway of life